2016
DOI: 10.1021/acssuschemeng.6b02351
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Bi Metal Deposition and g-C3N4 Coating on Bi2WO6 Microspheres for Efficient Visible-Light Photocatalysis

Abstract: A low-cost semiconductor-based photocatalyst using visible light energy has attracted increasing interest for energy generation and environmental remediation. Herein, plasmonic Bi metal was deposited in situ in g-C3N4@Bi2WO6 microspheres via a hydrothermal method. As an electron-conduction bridge, metallic Bi was inserted as the interlayer between g-C3N4 and the surface of Bi2WO6 microspheres to enhance visible light absorption due to the surface plasmon resonance (SPR) effect and facilitate efficient electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(89 citation statements)
references
References 48 publications
5
79
0
Order By: Relevance
“…(a,b) SEM images, (c) EDX spectrum, and (d) TEM image of 1.0CdS/Bi 2 MoO 6.The UV-Vis absorption spectra of Bi 2 MoO 6 , CdS, and 1.0CdS/Bi 2 MoO 6 are illustrated inFigure 3. Pure Bi 2 MoO 6 and CdS exhibit good absorption in the visible light region, consistent with the previous reports[18,37,40]. Notably, 1.0CdS/Bi 2 MoO 6 presents better optical absorption than Bi 2 MoO 6 , indicating that 1.0CdS/Bi 2 MoO 6 possesses a better ability to harvest sunlight.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…(a,b) SEM images, (c) EDX spectrum, and (d) TEM image of 1.0CdS/Bi 2 MoO 6.The UV-Vis absorption spectra of Bi 2 MoO 6 , CdS, and 1.0CdS/Bi 2 MoO 6 are illustrated inFigure 3. Pure Bi 2 MoO 6 and CdS exhibit good absorption in the visible light region, consistent with the previous reports[18,37,40]. Notably, 1.0CdS/Bi 2 MoO 6 presents better optical absorption than Bi 2 MoO 6 , indicating that 1.0CdS/Bi 2 MoO 6 possesses a better ability to harvest sunlight.…”
supporting
confidence: 90%
“…In recent years, the semiconductor-based photocatalysis as a green oxidation technology, has made significant developments for treating water pollutions [3][4][5][6][7][8][9][10]. Bismuth (III)-based semiconductors (e.g., BiOX (X = Cl, Br, I) [11][12][13], Bi 2 MoO 6 [14][15][16][17], and Bi 2 WO 6 [18]) have been emerging as kinds of high-efficiency photocatalysts. Among them, Bi 2 MoO 6 as a good visible-light-driven (VLD) photocatalyst, has been one of the focal research points in the area of photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…For pure BWO, the photocurrent intensity decreases with irradiation time, this experimental phenomenon is similar to previous research. 48,49 The reason may be due to the fact that photo-generated electrons in the inner layer of Bi 2 WO 6 need to overcome a long migration distance to reach the surface, and electrons can accumulate and recombine with holes during the irradiation time. 50 However, the photocurrent of BWO/BENT-30% kept constant with time and was higher than those of pure BWO and BWO/BENT-50%.…”
Section: Photocatalytic Oxidation Performancementioning
confidence: 99%
“…[1][2][3][4][5][6] Because of its unique structure, [7][8] Bi 2 WO 6 has been studied by many researchers on photocatalytic degradation. [9][10][11][12][13] In order to further improve the photocatalytic ability, many methods have been used from different aspects. The effects of different Bi 2 WO 6 morphologies on toluene degradation efficiency were investigated by Zhu et al, which showed that sheet-Bi 2 WO 6 catalyst had the best photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%